2014
DOI: 10.1097/nen.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte Gap Junction Loss and Disconnection From Reactive Astrocytes in Multiple Sclerosis Gray Matter

Abstract: Gap junctions are essential for glial cell function and have been increasingly implicated in multiple sclerosis (MS). Because increasing cortical abnormalities correlate with disease progression and cognitive dysfunction, we examined the expression of oligodendrocytic connexin32 (Cx32) and Cx47 and their astrocytic partners Cx30 and Cx43 in cortical lesions and normal-appearing gray matter (NAGM) in MS patients. Postmortem brain tissue samples from 9 MS cases were compared with 10 controls using real-time poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 82 publications
5
61
0
Order By: Relevance
“…This suggests that EAAT2 expression might be reduced in individual astrocyte as observed for CX43. Taken together, our analysis demonstrates that CX43, the major gap junction protein expressed by astrocytes and involved in the formation of the astrocyte syncytium, is downregulated in MS NAGM most prominently in layers III-V. A recent study identified a higher CX43 expression in MS cortical NAGM in comparison to control samples (Markoullis et al, 2014). Whether this discrepancy is due to the smaller sample number investigated or to the heterogeneous expression of CX43, which we also observed in control cases, cannot be verified.…”
Section: Cx43 Protein Reduction In Ms Nagm Is Characterized By Its Losupporting
confidence: 57%
“…This suggests that EAAT2 expression might be reduced in individual astrocyte as observed for CX43. Taken together, our analysis demonstrates that CX43, the major gap junction protein expressed by astrocytes and involved in the formation of the astrocyte syncytium, is downregulated in MS NAGM most prominently in layers III-V. A recent study identified a higher CX43 expression in MS cortical NAGM in comparison to control samples (Markoullis et al, 2014). Whether this discrepancy is due to the smaller sample number investigated or to the heterogeneous expression of CX43, which we also observed in control cases, cannot be verified.…”
Section: Cx43 Protein Reduction In Ms Nagm Is Characterized By Its Losupporting
confidence: 57%
“…To our knowledge, we are the first to show that peripheral axon injury can lead to an increase in Cx32 protein expression in the central nervous system and that, in the spinal cord, OL progenitor cells express Cx32. Similar to previous reports [8, 15] we observed Cx32 expression in both GM and WM subregions of the spinal cord with Cx32 expression was found in the processes and cell bodies of OPCs and on the perimeter of mature OLs [21,22] expressing CC1 or TrkB.…”
Section: Discussionsupporting
confidence: 91%
“…These glial cell changes appear to contribute to neuronal survival and regeneration [4,6], yet the specific roles served by the activation of astrocytes, microglia as well as oligodendrocytes (OLs) following peripheral axon injury are poorly understood. In particular, the plasticity of cells in the OL lineage is not well studied, yet the dysregulation of OLs contributes to demyelinating disorders [7,8], mood disorders [9], and lack of recovery following both traumatic brain injury and spinal cord injury [10,11]. Therefore a better understanding of the many factors that influence these cells has important clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Seizure activity could also arise as a result of loss of oligodendrocyte Cxs and reduction of Cx43 expression as observed in immune‐mediated mouse models of MS (Brand‐Schieber et al, ; Markoullis et al, ). Furthermore, demyelinating MS lesions show evidence of GJ dysregulation, where inflamed white matter tracts and adjacent normal appearing tissue exhibit decreased Cx43 expression and oligodendrocyte uncoupling from reactive astrocytes (Markoullis et al, ; Markoullis et al, ). In addition, MS patients are three to six times more likely to develop epilepsy than the overall population (Poser & Brinar, ).…”
Section: A Little Too Excited: Connexin and Pannexin Dysregulation Anmentioning
confidence: 99%